The complete genome sequence of the plant growth-promoting bacterium Pseudomonas sp. UW4. - Jin Duan (Public Library of Science (PLoS), 2013)
The plant growth-promoting bacterium (PGPB) Pseudomonas sp. UW4, previously isolated from the rhizosphere of common reeds growing on the campus of the University of Waterloo, promotes plant growth in the presence of different environmental stresses, such as flooding, high concentrations of salt, cold, heavy metals, drought and phytopathogens. In this work, the genome sequence of UW4 was obtained by pyrosequencing and the gaps between the contigs were closed by directed PCR. The P. sp. UW4 genome contains a single circular chromosome that is 6,183,388 bp with a 60.05% G+C content. The bacterial genome contains 5,423 predicted protein-coding sequences that occupy 87.2% of the genome. Nineteen genomic islands (GIs) were predicted and thirty one complete putative insertion sequences were identified. Genes potentially involved in plant growth promotion such as indole-3-acetic acid (IAA) biosynthesis, trehalose production, siderophore production, acetoin synthesis, and phosphate solubilization were determined. Moreover, genes that contribute to the environmental fitness of UW4 were also observed including genes responsible for heavy metal resistance such as nickel, copper, cadmium, zinc, molybdate, cobalt, arsenate, and chromate. Whole-genome comparison with other completely sequenced Pseudomonas strains and phylogeny of four concatenated "housekeeping" genes (16S rRNA, gyrB, rpoB and rpoD) of 128 Pseudomonas strains revealed that UW4 belongs to the fluorescens group, jessenii subgroup.